2003
DOI: 10.1002/jgm.336
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV‐1 replication in primary human T cells transduced with an intracellular anti‐HIV‐1 p17 antibody gene

Abstract: The expression of the anti-HIV-1 gag p17 scFv/Ckappa gene construct in primary human T cells renders these cells resistant to HIV-1 and points to the potential clinical usefulness of this gene construct for anti-HIV-1 gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…In this study, we demonstrated that the expression of 2LTRZFP-GFP, in the nucleus of human T-lymphocytic cells, markedly inhibited viral replication and integration as measured by the p24 antigen assay and Alu-gag qPCR, respectively. The HIV-1 integrase recognition sequence is highly conserved and is processed by HIV-1 IN in the early phase of viral replication (LaFemina et al, 1991;Vink et al, 1991;van den Ent et al, 1994;Yoshinaga and Fujiwara, 1995;Katzman and Sudol, 1996;Balakrishnan and Jonsson, 1997). Although certain integrase inhibitors are currently being approved and used for the treatment of HIV-1-infected FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that the expression of 2LTRZFP-GFP, in the nucleus of human T-lymphocytic cells, markedly inhibited viral replication and integration as measured by the p24 antigen assay and Alu-gag qPCR, respectively. The HIV-1 integrase recognition sequence is highly conserved and is processed by HIV-1 IN in the early phase of viral replication (LaFemina et al, 1991;Vink et al, 1991;van den Ent et al, 1994;Yoshinaga and Fujiwara, 1995;Katzman and Sudol, 1996;Balakrishnan and Jonsson, 1997). Although certain integrase inhibitors are currently being approved and used for the treatment of HIV-1-infected FIG.…”
Section: Discussionmentioning
confidence: 99%
“…However, RNA approaches may be limited by escape mutations in the site-targeting regions, even without the changing of encoded protein. Many protein interference strategies involve trans-dominant negative mutants (Liem et al, 1993) and single-chain variable fragments (scFvs) to inhibit the function of intracellular target proteins in specific cellular compartments, such as IN (Levy-Mintz et al, 1996), reverse transcriptase (RT) (Shaheen et al, 1996), Rev (Vercruysse et al, 2010), gp120 (Marasco et al, 1993), and Gag p17 (Tewari et al, 2003). However, the reducing environment in the cytosol is an obstacle to the formation of disulfide bonds required for scFv function.…”
Section: Introductionmentioning
confidence: 99%
“…24 In another example, retroviral plasmid-based delivery was used to express intrabodies to the a-HIV-1 Gag p17 protein in the cytoplasm of primary human T cells and in Jurkat cells (a human CD4(+) T cell line). 25 When these cells were challenged with several strains of HIV-1, replication was strongly inhibited, although the degree of resistance varied and was not efficient in cells that sustained high viral replication. The inhibition was at post-entry and reverse transcription levels, as only p24 and not proviral DNA differed between the scFvtransduced human primary T cells and control.…”
Section: Intrabodies Against Viral or Viral-related Host Proteins Canmentioning
confidence: 99%
“…To date, there are no available data about the effect of nuclear scFv fragments in viral potyvirus infections, although the potential of nuclear scFvs to interfere with HIV replication function has been reported (Sibler et al. , 2003; Tewari et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%